An Investigation into the Phytochemical Content, Antibacterial Eﬀect, and Antioxidant Capacity of the Ethanol Extract of Salacca wallichiana Mart. Peels - Tran Thi Cam Thi; Nguyen Trung Quan; Hoang Thanh Chi; Bui Thi Kim Ly (European Journal of Biology)
Objective: Salacca wallichiana Mart. is a prominent fruit-bearing tree distributed in Southeast Asia and used in treating many diseases and folk remedies. Thus far, only phytochemical composition-related research has been carried out on this plant, while the other bioactivities retarding its applicability in orthodox medicine have been ignored. Screening for the various bioeﬀects is needed to verify the authenticity of the medicinal activities of plants.Materials and Methods: Following Ciulei separation, the phytochemical contents of the fruit peel extracts were determined. The antioxidant eﬀect was evaluated by performing the free radical scavenging and potassium ferricyanide-reducing antioxidant power assays. Agar diﬀusion and broth dilution methods were used to ascertain the antibacterial capacity, and then the minimal inhibitory concentration (MICs) and MBCs were calculated.Results: The results illustrated a robust free radical scavenging but a weak reducing activity. The MIC against Gram-positive bacteria was <4 mg/mL. The phytochemical composition included tannins and ﬂavonoids, cardiac glycosides, organic acids, and reducing sugars.Conclusion: The extracts of S. wallichiana peels demonstrated a potential antioxidant activity along with lethality against Gram- positive bacteria, which was attributed to the diversity in the contents of secondary metabolites.